2020
DOI: 10.1002/mmce.22436
|View full text |Cite
|
Sign up to set email alerts
|

Graphene based metasurface with near unity broadband absorption in the terahertz gap

Abstract: This paper reports a novel graphene metasurface exhibiting near-unity absorption over a wide bandwidth of 9.74 THz ranging from 2.06 to 11.80 THz with a fractional bandwidth of 140.86% with respect to the center frequency of 6.93 THz within the terahertz gap of the electromagnetic spectrum. The proposed structure consists of two layers of graphene separated by silicon dioxide (SiO 2). On the top of SiO 2 , a modified fractal-shaped 1 nm thick graphene pattern is deposited while a square-shaped graphene pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 60 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…14 Ghosh et al presented a near-unity graphene metamaterial-based absorber in THz-gap with nearperfect absorption in 9.74 THz bandwidth with possible applications in next-gen 5G communication devices. 15 Sharma and coauthors presented magnetically tunable metasurface consisting of InSb-patched, InAs-patched, and unpatched pixels with an average tuning rate of 0.3 THz T −1 . 16 We presented a sensor to detect glucose levels in human blood so that the severity of diabetic patients can be determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Ghosh et al presented a near-unity graphene metamaterial-based absorber in THz-gap with nearperfect absorption in 9.74 THz bandwidth with possible applications in next-gen 5G communication devices. 15 Sharma and coauthors presented magnetically tunable metasurface consisting of InSb-patched, InAs-patched, and unpatched pixels with an average tuning rate of 0.3 THz T −1 . 16 We presented a sensor to detect glucose levels in human blood so that the severity of diabetic patients can be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Abdulkarim et al reported a square‐shaped water metamaterial‐based perfect solar absorber in a microwave regime with ultra‐broadband absorption response and with possible applications in the energy harvesting field 14 . Ghosh et al presented a near‐unity graphene metamaterial‐based absorber in THz‐gap with near‐perfect absorption in 9.74 THz bandwidth with possible applications in next‐gen 5G communication devices 15 . Sharma and coauthors presented magnetically tunable metasurface consisting of InSb‐patched, InAs‐patched, and unpatched pixels with an average tuning rate of 0.3 THz T −1 16 …”
Section: Introductionmentioning
confidence: 99%
“…Frequency selective surface (FSS) is widely used in wireless and satellite communication as a periodic surface that can transmit or reflect the electromagnetic (EM) signal. 1 FSS founds different applications as microwave absorber, 2,3 radar cross section reduction, 4 antenna radome, 5 polarization converter, 6 sub reflector in cassegrain horn, 7 EM cloaking, 8 and as antenna superstrate for directivity enhancement. 9 Recently, circular array radiation theory is applied to represent the scattered field from a conducting cylindrical surface and the theory is extended for concentric array geometry to realize active cloaking at microwave frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In the terahertz frequency band, graphene-based metasurface design is suitable for antennas and absorbers. [3][4][5] In theory, the properties of new graphene can evole into the properties of bulk graphite in less than 10 layers. 6 In this paper, multilayer graphene specimen was prepare from bulk graphene crystals by mechanical exfoliation method.…”
Section: Introductionmentioning
confidence: 99%